Consumer Satisfaction, Consumer-Brand Identification, and Repurchase Intention - Auliya Nurmalasari; Nikodemus Hans Setiadi Wijaya (Jurnal Maksipreneur, 2022)
This study proposes whether consumers will be loyal to a product with a brand that they have just bought and tried by knowing their repurchase intention. This study unfolds consumer satisfaction and consumer brand identification as the factors which can influence repurchase intention. A total of 177 samples were used. Path analysis in WarpPLS was used to examine the proposed hypotheses. The results showed a positive relationship influence of consumer satisfaction on repurchase intention. The results also showed a positive consumer-brand identification on repurchase intention. However, consumer-brand identification failed to moderate the relationship between customer satisfaction and repurchase intention.